SYMPTOMATIC DISCOID MENISCUS: A CASE SERIES - Asep Santoso, MD; Erwin Saspraditya; Muhammad Nagieb; Gilang Persada Aribowo; Iwan Budiwan Anwar; Tangkas SMHS Sibarani (Indonesian Hip and Knee Society (IHKS), 2021)
Background: Discoid meniscus is a rare entity of knee pathology. The discoid meniscus can be encountered incidentally during a treatment of another knee pathology as an asymptomatic entity or can be a symptomatic pathology which warrant treatment Case presentation: There were 8 cases of symptomatic discoid meniscus reported in this retrospective case series. The symptoms presented at age range 16-47 year-old. Majority of the case (6 of 8) are lateral discoid meniscus with female gender predominant. Complete type of discoid meniscus was also found in 6 of 8 cases. There were 5 cases of ruptured discoid meniscus, three of them needed repair. Conclusions: Symptomatic discoid meniscus can be presented on wide range of age of patients. We found female gender, discoid lateral meniscus, and complete type are the predominant pattern of discoid meniscus cases presentation.